KUALITAS KEHIDUPAN KERJA DAN KOMITMEN ORGANISASI - Liswandi Liswandi (JURNAL LENTERA BISNIS, 2016)
The objective of this study is to analyze the literatures on the relationship between quality of work life (QWL) and organizational commitment (OC). QWL has become crucial issue and popular topic nowadays since it is considered that it could build employees’ organizational commitment and performance. The implementation of good QWL is not considered to have good impacts to OC only but also to productivity and efficiency of the organizations. The organizations or companies should consider these two variables to be determinants for the organizations or companies in achieving their goals. Keywords: Quality of Work Life, Organizational Commitment, QWL Elements, and Organizational Commitment Dimensions